2015
DOI: 10.1002/pbc.25617
|View full text |Cite
|
Sign up to set email alerts
|

Successful Radiofrequency Ablation for Recurrent Pulmonary Hepatoblastoma

Abstract: To the Editor: The optimal treatment of lung metastases in patients with hepatoblastoma is unclear. Minimally invasive surgical techniques are generally safe and effective, but morbidity can be significant and limited prospective data exist.[1] Radiofrequency ablation (RFA) is one of the several minimally invasive thermal-based technologies which have been safely and successfully used to treat primary and metastatic solid tumors.[2] We report here the first successful treatment of pulmonary metastasis in a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In 2008, Ye et al 14 reported a 2-year-old boy with recurrent HB after liver resection treated by percutaneous RFA, and there was no imaging evidence of recurrence after a follow-up of 2 years. Recently, Dunn et al 19 demonstrated another successful treatment of pulmonary metastasis of HB in a 2-year-old boy using RFA. Both research groups deemed RFA to be a promising technique in children with recurrent HB.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Ye et al 14 reported a 2-year-old boy with recurrent HB after liver resection treated by percutaneous RFA, and there was no imaging evidence of recurrence after a follow-up of 2 years. Recently, Dunn et al 19 demonstrated another successful treatment of pulmonary metastasis of HB in a 2-year-old boy using RFA. Both research groups deemed RFA to be a promising technique in children with recurrent HB.…”
Section: Discussionmentioning
confidence: 99%
“…1 HB usually lacks specific clinical manifestations in the early stage. Radical resection is the gold standard for the treatment of HB 2 , but usually, only approximately 30% of children have the chance of radical resection at the time of diagnosis because liver space-occupying is usually large in volume, the lesion range involves multiple lobes of the liver, and important structures such as the hepatic hilum cannot be preserved during the surgery, or enough normal liver tissue cannot be preserved due to the large range of resection. 3 Consequently, more than half of the children have lost the best surgical opportunity when they see a doctor, especially for children with advanced (stage III/IV) HB.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell transplantation and radiation therapy have been reported in several patients with unclear successes [12]. Advances in therapy for relapsed patients may require further research [13,14]. Thus it is significant to find the relevant factors for the recurrence of hepatoblastoma for further research.…”
Section: Introductionmentioning
confidence: 99%